2019
DOI: 10.1155/2019/4027976
|View full text |Cite
|
Sign up to set email alerts
|

Wheelchair Tilt-in-Space and Recline Functions: Influence on Sitting Interface Pressure and Ischial Blood Flow in an Elderly Population

Abstract: Pressure ulcers (PUs) result from localised injury to the skin and underlying tissue and usually occur over a bony prominence as a result of pressure, often in combination with shear forces. Both pressure magnitude and duration are thought to be key risk factors in the occurrence of PUs, thus exposing wheelchair-bound subjects to high risk of PU development. As a result, wheelchairs that incorporate tilt-in-space and recline functions are routinely prescribed to redistribute pressure away from their ischial tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…However, each of these studies relied on self-report measures of pressure relief practices, even though self-reported behaviour is known to be highly unreliable [ 31 ]. On the other hand, positive effects of a variety of pressure relief activities on actual pressure distribution, blood flow, and tissue oxygenation have been reported in healthy controls [ 45 ] as well as individuals with SCI [ 46 , 47 ]. In addition, Sonenblum and Sprigle [ 30 ] reported that wheelchair users with no PU history perform significantly more weight shifts than individuals with a history of recurrent pressure injuries.…”
Section: Discussionmentioning
confidence: 99%
“…However, each of these studies relied on self-report measures of pressure relief practices, even though self-reported behaviour is known to be highly unreliable [ 31 ]. On the other hand, positive effects of a variety of pressure relief activities on actual pressure distribution, blood flow, and tissue oxygenation have been reported in healthy controls [ 45 ] as well as individuals with SCI [ 46 , 47 ]. In addition, Sonenblum and Sprigle [ 30 ] reported that wheelchair users with no PU history perform significantly more weight shifts than individuals with a history of recurrent pressure injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of these power seat functions are recognized by the users who showed an agreement of 93-100% (Table 3). Furthermore, the benefits of powered seating functions have been documented in the scientific literature [17,25,26,[59][60][61][62][63][64]. This information must be disseminated to HP.…”
Section: Plos Onementioning
confidence: 99%
“…Although it is an aid in mobility that supports the independent movement of elderly individuals and conserves energy for caregivers, it must be custom fit for the users' varied needs and abilities [14]. Previous studies indicated whether the wheelchair was fit for reducing injury, increasing its effectiveness, and promoting quality of life [15][16][17][18]. Elderly individuals with disabilities, in particular, not only were disabled but also lost physical or cognitive functioning for which basic devices did not help to meet their needs.…”
Section: Introductionmentioning
confidence: 99%